OsATL38 mediates mono-ubiquitination of the 14-3-3 protein OsGF14d and negatively regulates the cold stress response in rice. (26th August 2021) - Cui, Li Hua; Min, Hye Jo; Yu, Seong Guan; Byun, Mi Young; Oh, Tae Rin; Lee, Andosung; Yang, Hee Woong; Kim, Woo Taek
Abstract: One of the major regulatory pathways that permits plants to convert an external stimulus into an internal cellular response within a short period of time is the ubiquitination pathway. In this study, OsATL38 was identified as a low temperature-induced gene that encodes a rice homolog of Arabidopsis Tóxicos en Levadura RING-type E3 ubiquitin (Ub) ligase, which was predominantly localized to the plasma membrane. OsATL38 -overexpressing transgenic rice plants exhibited decreased tolerance to cold stress as compared with wild-type rice plants. In contrast, RNAi-mediated OsATL38 knockdown transgenic progeny exhibited markedly increased tolerance to cold stress relative to that of wild-type plants, which indicated a negative role of OsATL38 in response to cold stress. Yeast two-hybrid, in vitro pull-down, and co-immunoprecipitation assays revealed that OsATL38 physically interacted with OsGF14d, a rice 14-3-3 protein. An in vivo target ubiquitination assay indicated that OsGF14d was mono-ubiquitinated by OsATL38. osgf14d knockout mutant plants were more sensitive to cold stress than wild-type rice plants, indicating that OsGF14d is a positive factor in the response to cold stress. These results provide evidence that the RING E3 Ub ligase OsATL38 negatively regulates the cold stress response in rice via mono-ubiquitination of OsGF14d 14-3-3 protein. Abstract : A RING-type E3 Ub ligase, OsATL38, negatively regulates the cold stress response via mono-ubiquitination of a 14-3-3 protein, OsGF14d, in rice.